FACTORS DETERMINING SATISFACTION WITH THE STUDIES OF THE STUDENTS OF SCHOOLS OF HIGHER EDUCATION - Indrasiene, Valdone; Merfeldaite, Odeta; Railiene, Asta; Jegeleviciene, Violeta; Zemaitaityte, Irena (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
In the modern world conditioned by scientific–technical progress and globalisation it is becoming tricky for schools of higher education to respond to continuously changing needs of the labour market, to secure the expectations of the students towards the selected sought education and its realisation in certain situations of activities. Satisfaction of students with the studies and employment of graduates becomes one of the key criteria of the quality of studies which influences the academic activity of universities. The study introduces the factors which determine the satisfaction of the final years students with their studies. Quantitative research was selected – a representative survey was performed. The study population consisted of the students of the Lithuanian higher schools (universities and colleges) (n=459). It has been established that the key factors in the selection of study programs (demand of the study program on the labour market, the self–set career goals, clear potentials for professional career and links between the personal needs and the program) demonstrates the ability of students to plan and make decisions regarding their careers. When selecting a study program, the factors orientated towards assessment of personal achievements and own attitudes towards the profession (the selected graduation exams and their results, the prestige of the profession and the leisure time likings) are not less important. The key factors of satisfaction with the selected study program relate to the fact that the study program contributes to personal development, to better employment and career prospective.  Students are satisfied with the selected study program because of favourable educational study environment, of a possibility to gain practical skills and of the applicable system of assessment.